Stages of Development of Uzbekistan Industry and Changes in It - Abdinazarova Xidoyatxon Oripovna (Genius Journals, 2023)
The article describes the stages of development of the industry of the Republic of Uzbekistan and its structural changes. In it, the structural changes of Uzbekistan's industry in 2005-2022 were studied and conclusions were drawn based on the observation of statistical data and economic geographical analysis
Keywords: Uzbekistan's industry; structure of industries